KUALITAS PELAYANAN WAITER DI RESTORAN MAKAN PLACE THE ZURI HOTEL PEKANBARU - ', Risdayanti; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research aims to determine the waiter service at the Place Restaurant, The Zuri Hotel Pekanbaru. Tangibility, Empathy, Reliability Responsiveness and Assurance. This research uses a qualitative method with a qualitative descriptive approach to describe and explain the situation that occurred by collecting data and information in the field. The key informants in this research are Food and Beverage Management, supervisors and consumers. In this research, the data collection techniques used were interviews, observation and documentation. Based on the research results, it can be concluded that having a uniform is mandatory, providing a comfortable restaurant space, prioritizing service, providing service in good language, providing solutions and providing good facilities for guests. Keywords: Service. Waiter, Restaurant, Hotel